Lead time management in the garment sector of Bangladesh: an avenues for survival and growth - Nuruzzaman, Md.; Haque, A. K. M. Ahasanul (EuroJournals Publishing, Inc., 2009)

(untitled)
Bangladesh has emerged as an important supplier of quality readymade garments in the global market. The spectacular growth of garment sector in Bangladesh in recent years has dramatically changed the landscape of export composition of the country. Once heavily dependent on exports of primary products lead by Jute, the economy of Bangladesh is now experiencing almost 76% export contribution from readymade garments (RMG). The sector has now occupied an important place in Bangladesh national economy. Nevertheless, all is not well in this sector. It faces numerous challenges and it is now on the crossroad with the phasing out of quota system, GSP facilities and new provisions of WTO. In this study attempts have been made to find out the ways to face the competitive business environment by the efficient management process towards the lead time reduction. The main purpose of this article is to analyse the business process of the garment sector to find out it’s lead time minimization process. The study has been concluded by the development of a new diagram of business process with the outcome that the other management process in the supply chain is an important factor rather than process management in the lead time minimization process.